(untitled) (Mūzikas akadēmijas raksti, 2024)
The musical life of large cities is frequently researched by European music historians. Riga is among these cities. During the 17th century when the Swedish Empire ruled over the Baltic Sea region, Riga was a part of Livland (nowadays the northern part of Latvia, or Vidzeme, and the southern part of Estonia). Outside this city, the musical culture in the towns of Livland was quite different. It is not as well documented as the music life of Riga. The main purpose of this article is to determine the significance of musical practices in several small towns in Livland and to research their reflection in accessible historical sources. The article gives an interdisciplinary overview of musical culture in the churches of three towns of Livland – Cēsis (historical Wenden), Limbaži (Lemsal) and Valmiera (Wolmar) during the second half of the 17th century. These towns were chosen considering the historical documents that have survived.